PENERAPAN PEMBELAJARAN FISIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X IPA SMA NEGERI 8 MAKASSAR - Akhfar, Mariani (OMEGA : JURNAL ILMU PENDIDIKAN DAN SAINS FISIKA, 2023)
This study aims (1) to determine the magnitude of the results of physics taught using the STAD type cooperative learning model. (2) To find out the average student's physics learning outcomes after reaching the KKM standard after being taught using the STAD type cooperative learning model.This research is a pre-experimental research. This study uses a research design of One – Group Pretest-Posttest Design. The population of this study were students of class X IPA SMA NEGERI 8 MAKASSAR, amounting to 199 people. The amount is divided into 6 classes. By means of total sampling, 33 people were selected for class X IPA2 as the experimental class. The instruments used are observation, tests, and lesson plans. The data obtained in two ways were analyzed by descriptive statistics and gain test.The results showed that the results of the circular motion learning of class X SMA NEGERI 8 MAKASSAR students using the STAD cooperative method were categorized as adequate. Among the 33 experimental class students, there were 29 students who scored above 75 or 87%. In contrast to the results of circular motion learning, the understanding of class X IPA2 SMA NEGERI 8 MAKASSAR without applying the STAD type cooperative technique is categorized as inadequate because the scores obtained by students have not reached the specified criteria, namely 87% of the number of students who scored 75 and above. Both methods are effectively applied in learning circular motion for class X IPA2 SMA Negeri 8 Makassar. In accordance with the results of this study, suggestions are proposed, namely physics teachers, especially teachers of class X IPA2 SMA Negeri 8 Makassar to apply the STAD type cooperative technique in learning physics in general and circular motion in particular because this technique is effective in improving student learning outcomes.